The resettlement of Ukrainians from Romania to Ukrainian SSR in 1944–1947 - Сорока Ю. (Видавничо-поліграфічний центр "Київський університет", 2017)
The article is dedicated to the following issues: the intervention of the soviet forces to Romania; Romanian reparations to USSR for the material losses during the Romanian occupation of the soviet territory; the resettlement of Ukrainians from Romania to Ukrainian SSR by the soviet authorities. The author analyzed the historiographical works that deal with said issues. The agreements between USSR and Romania are considered in the article. Those agreements have established the order of the supply delivery to USSR and the deportation order of Ukrainians and Russians from Romania as well as deportation of Romanians and Jews from the Western Ukraine. The soviet efforts in agitation and propaganda of socialism are examined in the article. In addition, the author considered the components of the Stalin's totalitarian politics of the resettlement and immigration of the Ukrainian population. The process, special aspects and tragic consequences of the resettlement are shown in the article as well as the attempts of the resettled people to return and the measures of the soviet government that were aimed at the unification of the people living in USSR. Main aspects of the further research of those issues are proposed.

Досліджено проблеми, пов'язані зі вступом радянських військ на територію Румунії та відшкодування збитків, учинених Румунією Радянському Союзу військовими діями та окупацією його території; розкрито питання переселення радянськими органами українців із Румунії в УРСР. Проведено аналіз історіографічних праць, присвячених зазначеній проблемі. Досліджено зміст відповідних угод між Румунією та СРСР щодо поставок товарів, їх реалізація і виконання рішень про обмін населенням української і російської національностей із території Румунії і румун та євреїв із західноукраїнських земель. Показано розмах агітаційної та пропагандистської діяльності відповідних радянських органів про так звані переваги соціалістичного будівництва в СРСР. Висвітлено основні чинники імміграційної політики сталінського тоталітарного режиму щодо України. Показано хід, особливості та трагічні наслідки переселення, намагання українців повернутися в обжиті краї, заходи влади, націлені на уніфікацію життя людей в межах радянської системи, визначено основні аспекти подальшого дослідження теми.
Переселення українців із Румунії в УРСР у 1944–1947 рр.
Keywords: Ukrainians; Romanians; agreement; resettlement; deportation; enforcement; protests; українці; Румунія; угода; переселення; примус; протести